Managing human resources - Sherman, Arthur W. (South-Western Publishing Co, 1992)
Managing Human Resources retains its unique orientation to overall practicality and real-world application. Practical tips and suggestions provide effective ways of dealing with problems in communication, leadership, discipline, performance appraisal, and compensation administration.